Official GRE Verbal Reasoning practice questions. Volume 1 : with practice for the analytical writing measure. - Educational Testing Service; Graduate Record Examinations Board (New York : McGraw Hill Education, 2017)
Provides former test questions with answers and explanations to help students master the Verbal Reasoning section of the GRE, and includes test-taking strategies and an overview of the GRE Analytical Writing section.
Overview of the GRE verbal reasoning measure -- Test content -- Question type 1 : reading comprehension -- Question type 2 : text completion -- Question type 3 : sentence equivalence -- Mixed practice sets -- Overview of the GRE analytical writing measure.
At head of title: ETS.
"150 real test questions with explanations--straight from the maker of the GRE General Test"--Cover.
Keywords: Graduate Record Examination -- Study guides; Reading comprehension -- Examinations -- Study guides; Educational tests and measurements -- Study guides; Universities and colleges -- Examinations -- Study guides